Hand hygiene in health care settings: the citizens’ point of view - Foà, Chiara; Tura, Grazia Antonella; Camelli, Claudia; Silingardi, Roberta; Malavolti, Monia; Kuenzer, Elisabeth; Carraro, Gabriella; De Paolis, Barbara; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The infection risk prevention is one of the main objectives of all health and sanitary systems, since the reduction of the healthcare associated infections is attainable goals through appropriate prevention strategies. Among these, proper hand hygiene of health care professionals and citizens (visitors/outpatients/caregivers, volunteers) is fundamental to reduce the spreading of micro organisms and prevent infections. The purpose of the study is indeed to explore the self-reported hand washing behavior of citizens who access to health facilities and the variables involved in it, using in particular the Theory of Planned Behaviour. Method: A quantitative research was lead using an anonymous questionnaire, filled out online by 195 citizens (53.6% Female). In the survey were included all the associations of volunteers, relatives and caregivers who cooperate in health care settings of Emilia Romagna Region (Italy). Results: This study has shown that hand hygiene is influenced by different socio-demographic (e.g. gender, age, education) and socio-cognitive variables (intention, attitude, subjective norms, control beliefs). In particular, citizens have a favorable attitude toward hands hygiene in healthcare settings, but they wash their hands more frequently in other contexts or in case of global infectious diseases. Conclusion: The study confirms that the Theory of Planned Behavior adequately explains the hand hygiene behavior in health care settings. Furthermore the threat of infection has a significant impact both on the intention and on the behavior. The results mostly interested those are involved in infectious risk giving the opportunity to intervene with targeted programs for the citizenship.